Researching gender violence feminist methodology in action - Hester, Marianne, 1955-; Malos, Ellen; Skinner, Tina, 1971- (Cullompton, UK ; Portland, Or. : Willan Pub., 2005)
This text focuses on research methodology and approaches in the complex and sensitive area of violence against women, and provides important insights into, and critical approaches to, the evidence base for policy and practice.
Methodology, feminism and gender violence / Tina Skinner, Marianne Hester and Ellen Malos -- Feminist quantitative methodology: evaluating policing of domestic violence / Sue Griffiths and Jalna Hanmer -- Researching people in power: practice, analysis and action / Tina Skinner -- Researching Asian children's experiences of domestic violence: the significance of cultural competence and shared ethnicities of participants in the research process / Umme Imam with Parveen Akhtar -- Conducting social research with young people: ethical considerations / Melanie McCarry -- Comparison and collaboration: researching young people's experiences and perceptions of violence in the family across China and the UK / Marianne Hester and Geetanjali Gangoli -- Researching women political prisoners in Northern Ireland: ethnographic problems and negotiations / Mary Corcoran -- Listening to women's voices: the participation of domestic violence survivors in services / Gill Hague and Audrey Mullender -- Researching violent fathers / Lynne Harne -- Balls and permissions: theorising the links between football and domestic violence / Jill Radford and Eve Hudson -- In memoriam: Sue Lee (1941-2002), her life, research and influence / Jill Radford and Nicole Westmarland.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Feminism -- Research; Women -- Violence against -- Research -- Methodology; Women; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; Electronic books; Electronic books